Relationship between arterial blood pressure and blood viscosity in spontaneously hypertensive rats treated with pentoxifylline; Biorheology; Vol. 53, iss. 2 - Plotnikov M. B.; Aliev O. I.; Nosarev A. V.; Sidekhmenova A. V.; Anfinogenova Ya. J. Yana Jonovna; Anishchenko A. M.; Pushkina E. V. (2016, 2016)
Title screen